FRAMING ANALYSIS ON PARTAI DEMOKRAT’S CAMPAIGN IN 2014 GENERAL ELECTION ISSUES IN KOMPAS AND JAWA POS - MARYAM, SITI KHADIJAH NUR (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Language, mass media, media discourse.Mass media as an integral part of society today, they use language to deliver their report and transfer their idea toward readers. Because of its complexity, the news makers have to select and rephrase reality. This technique is called as framing where the same topic will be given differently by the different newspaper, depends on its own perspective which is reflected by the use of language. Therefore, the position of mass media is constructing reality rather than merely informing the reality to the society.This research is about framing analysis in Jawa Pos and Kompas printed media reporting Partai Demokrat during the campaign’s period for general national election 2014. Since they are the oldest and the biggest newspapers in Indonesia, they tend to have a big power in creating a public opinion around the society. There are two problems to be solved, namely: how Kompas and Jawa Pos control their readers’ opinion through (1) their lexical choices; (2) their syntactical structures.This study uses qualitative approach in relation to the use of clear explanation about data to be analyzed. Content analysis is applied in this study to understand the data which is taken from news article in newspaper.This study reveals that in order to create public opinion towards Partai Demokrat, Jawa Pos use repetition words which consists of selected nouns, adjectives, and verbs with positive connotation meaning. Since then, Jawa Pos tries to support the currently ruling political party in Indonesia. Besides, Kompas tends to be a neutral media, by reporting Partai Demokrat with denotative meaning; therefore, it will reduce the ambiguity from the readers. From the syntactical problems, Jawa Pos as well as Kompas used active clauses more often than passive clauses. The active clauses used to foreground the actor. The most common actor is Susilo Bambang Yudhoyono (SBY) as the leader of Partai Demokrat is used to portray Partai Demokrat itself.The writer suggests that English Department students learn more about discourse analysis especially media discourse analysis. The writer also suggests that the next researcher conduct a research in more various aspects of linguistic tools in order to get more accurate and comprehensive conclusion.